AUDIUAL - Adam Siksik; Obada Qasrawi (My University, 2022)
Books were and still are one of the most important sources of joy or knowledge wither you want to read a book about mystery or a book about a guy who goes around the world in 80 days or simply wanna spend your time in an honest and harmless way books are always your go to destination. But with the invention of videos and the sites such as YouTube people slowly started going away from books and preferring to watch a video since it takes less effort. Here comes our project into play. Audiual is an application that has a wide variety of books that can be enjoyed by all kinds of people with books ranging from Romance,Mystery or Action. Audiual helps people enjoy books without even reading them where each book has its own content and audio that is played anytime a user clicks on a book. The user can also search for a book,add it to favourite or put it on his to watch later list.there is also a recommendation system for the user that works on his most recent book activities that helps him pick the most suitable books for him